Noah's ark - Spier, Peter; Revius, Jacobus, 1586-1658. (New York : Bantam Doubleday Dell, 1977)
Retells in pictures how a pair of every manner of creature climbed on board Noah's ark and thereby survived the Flood.
"A Doubleday Book for Young Readers."
Includes Peter Spier's translation of The flood by Jacobus Revius.
Caldecott Medal/Honor
Elem. School Library Collection
Wilson's Children
Booklist, February 1996
Keywords: Dutch poetry; Noah's ark -- Juvenile literature; Bible stories -- O.T.; Dutch poetry; Noah's ark; Noah's ark -- Pictorial works; Bible stories; Dutch poetry; Noah's ark; Noah's ark -- Pictorial works